Parliament, the Budget and Poverty in South Africa. A Shift in Power : A Shift in Power - Verwey, Len (Book collections on Project MUSE., 2009)
Effective and transparent government budgeting is vital to any democracy. In South Africa, massive poverty, inequality and unemployment remain, despite the successful political transformation, citizens and Parliament have a particularly important role to play in shaping budget policy and overseeing its implementation. South Africa reached a crossroads in fiscal governance when it passed the Money Bills Amendment Act in 2009, a law which granted Parliament strong powers to amend the budget prepared by the executive. This publication explores the content of the new law as well as the challenges.